Two’S Company, but Three’S No Crowd: Evaluating Exploratory Web Search for Individuals and Teams - Gonzalez-Ibanez, R (Emerald Group Publishing Ltd., 2015)
Purpose – The purpose of this paper is to investigate when and how people working in collaboration could be benefitted by an exploratory search task, specifically focussing on team size and its effect on the outcomes of such a task. Design/methodology/approach – The paper investigates the effects of team sizes on exploratory search tasks using a lab study involving 68 participants – 12 individuals, ten dyads, and 12 triads. In order to assess various factors during their exploratory search sessions, an evaluation framework is synthesized using relevant literature. The framework consists of measures for five groups of quantities relevant to exploratory search: information exposure, information relevancy, information search, performance, and learning. Findings – The analyses on the user study data using the proposed framework reveals that while individuals working alone cover more information than those working in teams, the teams (dyads and triads) are able to achieve better information coverage and search performance due to their collaborative strategies. In many of the measures, the triads are found to be even better than the dyads, demonstrating the value of adding a collaborator to a search process with multiple facets. Originality/value – The findings shed light on not only how collaborative work could help in achieving better results in exploratory search, but also how team sizes affect specific aspects – information exposure, information relevancy, information search, performance, and learning – of exploratory search. This has implications for system designers, information managers, and educators. © 2015, Emerald Group Publishing Limited.